Technospheric Mining of Critical and Strategic Metals from Non-Ferrous Slag - Lim, Bona (Curtin University, 2022)
The thesis contributes to the development of cleaner production in the mining industry by promoting technospheric mining of critical and strategic metals from non-ferrous slag. Specifically, the extraction of cobalt and nickel from nickel slag was studied from the literature review, experiment, interpretation, kinetic study, and mechanism investigation. Organic acid leaching with reagents such as a complexing agent and an oxidant successfully extracted cobalt and nickel from nickel slag.